Evidence for NQO1 and NQO2 catalyzed reduction of ortho- and para-quinone methides. (December 2013) - Kucera, H. R.; Livingstone, M.; Moscoso, C. G.; Gaikwad, N. W.
Abstract: NAD(P)H:quinone oxidoreductase (NQO1) and NRH:quinone oxidoreductase 2 (NQO2) catalyze the two-electron reduction of quinones and thereby prevent generation of toxic radicals. Quinone methides (QMs) covalently react with cellular macromolecules to form DNA adducts and/or protein conjugates resulting in toxicity and carcinogenesis. Based on similar structural features of quinones and QMs, it is logical to assume that NQO1 and/or NQO2 could also catalyze the two-electron reduction of QMs. However, hitherto the reduction of QMs, as both endogenous and/or exogenous biological substrates, by either NQO1/NQO2 has never been demonstrated. Here we show for the first time that both NQO1 and NQO2 can catalyze the reduction of electrophilic ortho- / para -QMs. The involvement of the enzyme in the reduction of p -cresol quinone methide (PCQM) and o -cresol quinone methide (OCQM) was demonstrated by reappearance of NQO1/NQO2-FAD peak at 450 nm after addition of the QMs to the assay mixture. Further reduction of methides by NQO1/NQO2 was confirmed by analyzing the assay mixture by tandem mass spectrometry. Preliminary kinetic studies show that NQO2 is faster in reducing QMs than its homolog NQO1, and moreover, ortho -QMs are reduced faster than para -QMs. Enzyme-substrate docking studies showed results consistent with enzyme catalysis. Thus, NQO1/NQO2 can play a significant role in deactivation of QMs.